THE INFLUENCE OF CONTENT MARKETING ON INSTAGRAM ON INTEREST IN BUYING WEDDING PACKAGES AT W BALI SEMINYAK - Wirata, I Nengah; Citrawati, Luh Putu; Darmiati, Made (Pusat Penelitian & Pengabdian kepada Masyarakat, Politeknik Pariwisata Bali, 2024)
Social media forums are communication tools used in the social process that can be accessed anywhere, anytime, and directly via the internet. One of the strengths of social media forums is their direct influence on the formation of consumer buying interest. W Bali-Seminyak is one of the companies engaged in the hospitality sector that also uses social media as a strategy to attract consumer interest. Although W Bali-Seminyak has used several social media forums as a means of building interaction with consumers, the selection of strategies in social media marketing forums with content marketing strategies is still rarely used. Based on this phenomenon, a study was conducted that aims to analyze the effect of content marketing on Instagram on the interest in buying wedding packages at W Bali-Seminyak. The analytical method used is descriptive quantitative analysis using validity test, reliability test, multiple linear regression analysis, t test, F test and coefficient of determination. The results of the study indicate that there is a positive influence between content marketing on the buying interest of prospective brides and grooms together at W Bali-Seminyak. owned by W Bali-Seminyak